2017
DOI: 10.3390/e20010009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimization of Trapezoidal Grooved Microchannel Heat Sink Using Nanofluids in a Micro Solar Cell

Abstract: Abstract:It is necessary to control the temperature of solar cells for enhancing efficiency with increasing concentrations of multiple photovoltaic systems. A heterogeneous two-phase model was established after considering the interacting between temperature, viscosity, the flow of nanofluid, and the motion of nanoparticles in the nanofluid, in order to study the microchannel heat sink (MCHS) using Al 2 O 3 -water nanofluid as coolant in the photovoltaic system. Numerical simulations were carried out to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…This special issue consists of nine articles that report on investigations dealing with heat and mass transfer and thermodynamic analysis of thermofluidic systems [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Most of these investigations are analytic or numerical [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Two of the investigations include experiments [ 36 , 39 ].…”
Section: The 9 Contributions Published In This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…This special issue consists of nine articles that report on investigations dealing with heat and mass transfer and thermodynamic analysis of thermofluidic systems [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Most of these investigations are analytic or numerical [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Two of the investigations include experiments [ 36 , 39 ].…”
Section: The 9 Contributions Published In This Special Issuementioning
confidence: 99%
“…Two of the investigations include experiments [ 36 , 39 ]. The main theme of four articles in this special issue is optimization of microchannels from both energetic and entropic perspectives [ 34 , 36 , 39 , 40 ]. Other areas that have been explored include the analysis and optimization of microreactors [ 33 ], simulation and thermal analysis of micro circular Couette flow [ 37 ], and thermodynamic analysis of various-shaped micro-scale thermoelectric coolers [ 38 ].…”
Section: The 9 Contributions Published In This Special Issuementioning
confidence: 99%
“…In recent years, a great number of studies have been conducted utilizing innovative geometries [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], employing liquid coolants with excellent thermal features [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], and applying micro-pin-fins [ 42 , 43 , 44 ] in order to improve the capabilities of microchannel heat sinks (MCHS) removing the heat generated by electronic chips.…”
Section: Introductionmentioning
confidence: 99%
“…Lu and Vafai [ 25 ] carried out a comparative study of MCHS with different layers. Wang et al [ 26 ] performed a numerical research on the thermal performance of MCHS with a series of trapezoidal grooves. Soleimanikutanaei et al [ 31 ] carried out a numerical study of the heat transfer enhancement through utilizing transverse microchannels in heat sinks.…”
Section: Introductionmentioning
confidence: 99%
“…For a constant pressure drop, a microchannel with a 70 • side angle in the optimum state has the maximum total thermal conductivity. A heterogeneous two-phase model was employed by Wang et al [13] to study the microchannel heat sink using an Al 2 O 3 -water nanofluid as a coolant in a photovoltaic system. The numerical results showed that the effects of flow field, volume fraction, and nanoparticle size on the heat transfer enhancement in an MCHS were governed by the ratio of Brownian diffusion and thermophoretic diffusion.…”
Section: Introductionmentioning
confidence: 99%